A case of atypically located leiomyoma mimicking axillary lymphadenomegaly - Mehmet Nuri Cevizci; Ali Fettah; Mehmet Eşref Kabalar (The Turkish Journal of Pediatrics)
Leiomyomas are benign smooth muscle tumors rarely seen in children and may occur anywhere in the body containing smooth muscle. Here, we report a case of a 4-year-old girl presenting with swelling in the left axillary region and with pain during arm movements. The solid mass in the axillary region was totally excised. The patient was discharged without complications on the same day.